Financial markets and institutions - Howells, Peter G. A.; Bain, Keith (Harlow : FT/Prentice Hall, 2004)
Looking at the subject from the economist's perspective, the book takes a practical, applied approach and theory is covered only where absolutely necessary in order to help students understand events as they happen in the real world. This fourth edition has been thoroughly updated to reflect the changes that have occurred in the financial system in recent years.
Includes bibliographical references and index.
oif 27/08/15
Loans
Keywords: Financial institutions; Finance; Financial markets